On Form : Poetry, Aestheticism, and the Legacy of a Word. - Leighton, Angela (OUP Oxford, 2008)
On Form assesses both the legacy of Victorian aestheticism and the nature of the literary. It tracks the development of the word 'form' since the Romantics and offers readings of, among others, Tennyson, Yeats, Stevens, and Plath. Original readings of poetry are combined with a powerful argument about the nature of aesthetic pleasure.